2008
DOI: 10.1016/j.jmarsys.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Tidal pumping and nutrient fluxes on Georges Bank: A process-oriented modeling study

Abstract: Process-oriented studies with the unstructured-grid, three-dimensional Finite-Volume Coastal Ocean Model (FVCOM) of Georges Bank were used to examine the importance of physical processes on the cross-isobath transport of nutrients onto the Bank. Starting from idealized vertical profiles of NO 3 constructed from summertime climatologic fields, the nutrient field was integrated in time using a conservative tracer equation with both homogenous and stratified initial hydrography and both tide and wind forcing. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…4), and also a larger volatility in chl-a in spite of similar volatilities in temperature and nutrients. A high volatility in biomass is predicted to signal dynamic chaos (Scheffer et al 2001) and support the finding that interaction patterns at shallow waters are qualitatively different from those at deep waters e.g., as in Malin et al (2005) and Hu et al(2008).…”
Section: Differences Between Regions In Coastal Waterssupporting
confidence: 73%
“…4), and also a larger volatility in chl-a in spite of similar volatilities in temperature and nutrients. A high volatility in biomass is predicted to signal dynamic chaos (Scheffer et al 2001) and support the finding that interaction patterns at shallow waters are qualitatively different from those at deep waters e.g., as in Malin et al (2005) and Hu et al(2008).…”
Section: Differences Between Regions In Coastal Waterssupporting
confidence: 73%
“…Tidal pumping is thought to be the primary mechanism by which cold, salty, nutrient-rich water is brought up onto the bank, primarily along the northern edge (Franks and Chen, 2001; Horne et al, 1989; Hu et al, 2008; Ji et al, 2008). The bulk of the new nitrate is presumably taken up by phytoplankton other than A. fundyense , given that it makes up such a small component of the autotrophic biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Tidal pumping provides a persistent source of nutrients from the adjacent deep basins (Franks and Chen, 2001; Horne et al, 1989; Hu et al, 2008; Ji et al, 2008). Phytoplankton chlorophyll is typically highest on the crest and decreases in the deeper areas along the periphery of the bank, with high rates of primary production throughout the year (O’Reilly et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above observations and the BNL-cyst distribution data presented here, it is suggested that the southerly extension of the MCC may periodically be associated with a high abundance of suspended cysts in the underlying BNLs. If the cysts are eventually carried farther south to the northern side of Georges Bank, strong tidal mixing and upwelling (Franks and Chen, 1996; Chen and Beardsley, 1998; Townsend and Thomas, 2001; Hu et al, 2008) could bring those cysts to the surface where favorable nutrient and light conditions would allow them to bloom. Obviously, this pathway of suspended cyst transport from the central gulf to Georges Bank is not resolved by the present data and a comprehensive assessment of that potential awaits further study.…”
Section: Discussionmentioning
confidence: 99%